Educational ranking model of faculties in Iranian universities of medical sciences - Hamid Ravaghi; Leila Janani; Reyhane Mohamadi; Ali Mazaherinezhad; Narges Rafiei (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: It is crucial to have a transparent and comprehensive tool in place to ensure accurate information on the educational performance of faculties. With this in mind, the aim of this study was to develop a model for ranking the educational performance of faculties in Iranian medical universities. Material & Methods: This study involved the development of an educational ranking tool for the faculties, which was carried out in 4 stages: compilation of indicators, conducting a focus group discussion, utilizing the Delphi technique, and finally consulting with an expert panel. In the given process, the tool's primary indicators were gathered based on various factors, such as the "educational ranking of medical sciences universities," the "ranking of educational services of universities," and the "postgraduate education performance evaluation system in medical sciences universities." These indicators were designed over a course of 17 sessions. After compiling the primary indicators, the indicators were thoroughly reviewed in four sessions in the presence of educational experts. Subsequently, the Delphi technique was employed, and eight expert panel meetings were held to finalize the indicators and areas, the weight of each indicator and domain, data collection methods, and the method of ranking the faculties. Finally, a scoring guide was prepared for all criteria to ensure a fair and objective evaluation process. Results: The educational ranking model of faculties was designed to evaluate three educational fields - "educational services", "postgraduate education", and "the educational field". The educational field was assessed based on 16 indicators in five areas, including education development, governance, education management, quality development of education, and moving in line with the comprehensive scientific map of the country. These indicators were carefully chosen to ensure a comprehensive evaluation of the faculties' educational excellence. The educational services sector has developed 11 checklists across five key areas: objective factors, reliability, accountability and responsibility, assurance, and empathy. Additionally, the evaluation of postgraduate education performance includes 36 indicators across seven areas: educational program, student evaluation, students, faculty members, educational resources, program evaluation, and senior and executive management. Conclusion: An educational ranking tool has been developed for faculties in medical science universities. This tool evaluates all educational fields of faculties, including educational services, postgraduate education, and the educational field. It also offers the possibility of comparing faculties within a university. The use of this ranking model can lead to improvements in both quantitative and qualitative educational indicators and ultimately improve the educational rank of the university among other medical science universities.